(untitled) (Research, Society and Development, 2022)
Aim: to perform a cross-cultural adaptation of the Assessment of Safe Nursing Care Questionnaire for Brazilian Portuguese. Method: methodological study developed in five stages: translation, evaluation by a committee of judges, back-translation, semantic analysis, and pre-test. A committee of judges performed validation; proportion of agreement of 80% was considered. The pre-test included 49 nurses from two teaching hospitals in the southeastern region of Brazil. Data were collected between October 2020 and July 2021. Descriptive statistics were used for data analysis. Results: the translation and back-translation steps were considered appropriate; face validation was performed through semantic, idiomatic, conceptual, and content equivalences. Five judges participated, and the proportion of agreement corresponded to a percentage greater than or equal to 80, and of the 32 items that make up the instrument, seven underwent modifications. It was possible to observe ease of understanding and acceptance of the questionnaire items during their application in the pre-test. Conclusion: the analysis by the committee of judges and the pre-test showed that the items are relevant to Brazilian culture and assessed the dimension proposed by the original instrument.